Indigenous Young People and Hyperincarceration in Australia. (December 2015) - White, Rob
This article describes and analyses the over-representation of Indigenous, young people in Australian juvenile justice. It contextualises this over-representation, through a brief discussion of colonialism and its continuing impacts. The concept of hyperincarceration is then used to describe the patterns of Indigenous detention, one that is overwhelmingly, disproportionate in terms of Indigenous status compared to non-Indigenous status. This article provides recent empirical evidence of the gross over-representations of Indigenous young people, especially in the harshest parts of the juvenile justice system. Alternative forms of intervention, such as justice reinvestment, are briefly discussed.